Making news of police violence : a comparative study of Toronto and New York City - Ross, Jeffrey Ian (Praeger, 2000)
Using both qualitative and quantitative research, this work seeks to understand how, and under what conditions, excessive police violence leads to public outcry, and subsequent police responses to demands for change.